THE HARMONY OF FORMING A CULTURE OF THINKING AMONG YOUTH WITH SPIRITUAL AND MORAL FACTORS (Scientific journal of the Fergana State University, 2026)
This article provides a scientific and theoretical analysis of the process of forming a culture of thinking among youth and its integral relationship with spiritual and moral factors. The study раскрывает the content of the culture of thinking, its role in personal development, as well as the importance of spiritual and moral values in developing young people’s abilities for independent, critical, and creative thinking. It also highlights the role of national and universal values, moral norms, the social environment, and the educational process in shaping a culture of thinking among youth. The article proposes practical recommendations and effective ways of utilizing spiritual and moral factors in the educational process. The results of the study contribute to the formation of a healthy worldview among young people and to the enhancement of their social activity.